2014
DOI: 10.1167/iovs.14-14061
|View full text |Cite
|
Sign up to set email alerts
|

Mitigation of Oxygen-Induced Retinopathy in α2β1 Integrin-Deficient Mice

Abstract: PURPOSE. The a2b1 integrin plays an important but complex role in angiogenesis and vasculopathies. Published GWAS studies established a correlation between genetic polymorphisms of the a2b1 integrin gene and incidence of diabetic retinopathy. Recent studies indicated that a2-null mice demonstrate superior vascularization in both the wound and diabetic microenvironments. The goal of this study was to determine whether the vasculoprotective effects of a2-integrin deficiency extended to the retina, using the oxyg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 45 publications
1
8
0
Order By: Relevance
“…The complete revascularization of avascular areas argued against a strong anti-angiogenic activity of Gpr116, as seen in the case of severe blockade of VEGF [ 53 ]. The absence of tuft formation is, in turn, one of the more remarkable findings in comparison with previously described OIR phenotypes (such as in [ 54 ]), and seems as extensive as the A2A receptor and N-CAM mutants [ 49 ][ 50 ]. It is also the only phenotype reported to date in Gpr116 knockouts that presents a graded response, with intermediate effect in the heterozygous littermates.…”
Section: Discussionsupporting
confidence: 55%
“…The complete revascularization of avascular areas argued against a strong anti-angiogenic activity of Gpr116, as seen in the case of severe blockade of VEGF [ 53 ]. The absence of tuft formation is, in turn, one of the more remarkable findings in comparison with previously described OIR phenotypes (such as in [ 54 ]), and seems as extensive as the A2A receptor and N-CAM mutants [ 49 ][ 50 ]. It is also the only phenotype reported to date in Gpr116 knockouts that presents a graded response, with intermediate effect in the heterozygous littermates.…”
Section: Discussionsupporting
confidence: 55%
“…In view of its high expression on keratinocytes and its identification on dermal fibroblasts, the finding that α2β1 was not involved in keratinocyte migration or dermal fibroblast wound closure in vivo was surprising (Parks, 2007), even though increased neoangiogenesis was observed during wound healing (Grenache et al, 2007;Zweers et al, 2007). In a more recent study, reduced pathological neovascularization in integrin α2 −/− mice was observed in a model for retinopathy (Madamanchi et al, 2014a). The absence of α2 is known to delay fibrosis and glomerular damage in experimental kidney disease models, including the Alport syndrome mouse model (Borza et al, 2012;Rubel et al, 2014).…”
Section: Integrin α2β1mentioning
confidence: 99%
“…[63][64][65] Many human diseases, including retinopathies, have been associated with altered integrin-mediated adhesion and migration. [66][67][68] Therefore, there has been strong interest in understanding and potentially targeting integrin-mediated FIGURE 6. b1-integrin and MMP-2 colocalization is increased in MIO-M1 cells stimulated with IGF-1. The top two rows show representative images obtained by confocal microscopy.…”
Section: Discussionmentioning
confidence: 99%